Бенедикт Карпцов - Кобилецький, М.; Kobyletski, M. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті висвітлюється наукова та професійна діяльність відомого дослідника та засновника німецької науки кримінального та кримінально процесуального права Бенедикта Карпцова. Праця Бенедикта Карпцова «Practica nova» вважається однією з найкращих юридичних праць Європи періоду раннього нового часу. Заслуга Карпцова полягала у поєднанні традицій німецького права, зокрема кримінального процесу за кодексом Карла V «Кароліна» та Саксонським процесуальним правом. Проаналізовано найвідоміші наукові праці Бенедикта Карпцова. Показано вплив праць Бенедикта Карпцова на кодифікацію українського права. Праці Бенедікта Карпцова використовувались у судах Києва, Львова та судах інших українських міст України, що володіли магдебурзьким правом.The article sheds the light on the scientific and professional activities of Benedict Karptsov, a famous researcher and the founder of the German Scientific school of criminal and criminal-procedural law. He, unlike other German legal experts in XVI-XVII-th cent., had good judicial education and experience of the legal practice in courts. He is considered to be an outstanding specialist in criminal law and procedure, and the founder of the German scientific school of criminal law. The work by Benedict Karptsov «Practica nova» is considered to be one of the best legal papers in Europe of the early period of modern times. It was the merit of Karptsov that he combined traditions of German law, especially criminal procedure code by Carl V «Carolina» and the Saxon procedural law. The article offers insights into other major works by B.Karptsov, indicating to their impact on the codification of the Ukrainian law. Works by Benedict Karptsov were widely used in the German lands, in other European countries, as well as in Ukraine. The works by Benedict Karptsov were used in the courts of Kyiv, Lviv and other Ukrainian city courts, which were granted Magdeburg Law. These works were also familiar to the representatives of the Cossacks authorities.
Benedyct Karptsov
Keywords: магдебурзьке право; римське право; Саксонське Зерцало; кримінальне право; судочинство; Німеччина